SPECIFIC CHARACTERISTICS OF PEDAGOGICAL TECHNOLOGIES - Khatamova, Zumrad Nazirjonovna; Almamatova , Nurkhan (Innovative Development in Educational Activities, 2023)
In the article, the concept of pedagogical technology, its factors of origin, necessity are discussed, and the necessity of its formation is also touched upon.